Effect of Fukushima Accident on Tourists Based Coastal Belts of Chittagong City, Bangladesh (The Chittagong University Journal of Science, 2018)
This research work was aimed to obtain the radioactive exposure of naturally occurring and anthropogenic radioactive materials in sediment samples from the coastal belts of Chittagong city due to the Fukushima nuclear accident. The activity concentration, absorbed outdoor and indoor dose rates, annual effective dose rates and the radiation hazard indices from these samples were calculated. The correlation coefficient and Chi-square value per degree of freedom were also determined. A strong correlation between radium equivalent activity and activity of 232Th was obtained in the Bay of Bengal. However, a very poor correlation was observed for radium equivalent activity and activity of 40K in both the study areas. The Chi-square value per degree of freedom (χ2R) for 226Ra, 232Th and 40K were respectively 70.244, 77.168 and 1.87 for the Karnaphuli River samples and 38.091, 62.023 and 2.06 for the Bay of Bengal samples. No artificial radionuclide was detected in the samples measured from the study areas. No radiation threat level is obtained on the study areas due to the nuclear explosion at Fukushima.The Chittagong Univ. J. Sci. 40 : 111-136, 2018